Conhecimento, tecnologia e futuro: análise do cenário de inovação dos países emergentes - Silva, Diogo Cortiz da (2015)
This research discusses the role of technological innovation to ensure economic growth and the autonomy of nations. For these purposes, it investigates the current process of technological development and its relationship with the current scientific model. This work considers scientific knowledge as a key pillar in any innovation process, once it is responsible for finding, identifying and extracting value from new phenomena. It starts with the hypothesis that there is still a degree of concentration of scientific dynamics in certain locations, such as in the United States, Europe and some Asian countries, despite the fact that Internet have created a global network for information exchange. This situation occurs because tacit knowledge one kind of knowledge that depends on experience and is the major driver of innovation demand time, interaction and experimentation for its transfer and acquisition, which demonstrates the limitations of the Internet. This research focuses on the United States, European Union and emerging countries that are part of the BRICKs (Brazil, Russia, India, China and South Korea), collecting data on scientific production and innovation of each one of them, making it possible to identify the key factors and strategies that put some of these nations in the leading position in innovation. This research shows that Brazil has a fragile ecosystem of innovation due to low scientific production indicators, low quality of education system and especially absence of long-‐term planning to priority areas. Finally, we point out some trends such as entrepreneurship, interdisciplinary education and collaborative research to create possibilities for acquiring and sharing knowledge, which is essential to stimulate innovation in an emerging nation